Efektivitas Model Think Talk Write (TTW) terhadap Kemampuan Menulis Teks Anekdot Siswa Madrasah Aliyah - Ayu Siti Aisyah; Tri Astuti; Indah Puspita Sari; Agung Nugroho (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2021)
This study aims to determine the effectiveness of the Think Talk Write (TTW) model on the ability to write anecdotal texts for class X MA Negeri 1 (Model) Lubuklinggau students. The research method used was quasi-experimental. Test data analysis techniques with steps to determine the average value and standard deviation, normality test, t test and non-test data techniques (Questionnaire). The results showed that the results of hypothesis testing and data analysis obtained tcount = 26,325 and Sig (2-tailed) that is 0.000.0 <0.05. Meanwhile, the non-test data (questionnaire) obtained from the recapitulation of the positive response data from students showed that the answers strongly agreed and agreed with 54.8%, in the good category. In conclusion, the use of the Think Talk Write (TTW) model is effective on the ability to write anecdotal texts for class X MA Negeri 1 (Model) Lubuklinggau students. Keywords: Effectiveness of Think Talk Write (TTW) Model, Ability to Write Anecdo Text